Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1097/00005344-199712000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Polysaccharide Fucoidin on Myocardial Ischemia-Reperfusion Injury in Rats

Abstract: We tested whether polysaccharide fucoidin, which inhibits leukocyte rolling in the mesenteric venule, has protective effects in the rat myocardial 30-min ischemia and 6-h reperfusion injury model. Intravenous infusion of fucoidin (27 microg/kg/min from 10 min before to 6 h after reperfusion) significantly attenuated myocardial infarct size 6 h after reperfusion. In this ischemia and reperfusion heart model, expression of P-selectin (determined immunohistochemically) was observed on the venular endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 49 publications
6
38
0
1
Order By: Relevance
“…Several studies have demonstrated that intestinal ischemi a! reperfusion injury in rats is dependent on neutrophil recruitment (25)(26)(27)(28)(29)(30)(31). Postischemic treatment of animals with reparixin inhibited the increase of vascular permeability and neutrophil recruitment in a dose-dependent manner (23).…”
Section: Lps-induced Blood Neutrophilia In Rats Four Hours After Lmentioning
confidence: 99%
“…Several studies have demonstrated that intestinal ischemi a! reperfusion injury in rats is dependent on neutrophil recruitment (25)(26)(27)(28)(29)(30)(31). Postischemic treatment of animals with reparixin inhibited the increase of vascular permeability and neutrophil recruitment in a dose-dependent manner (23).…”
Section: Lps-induced Blood Neutrophilia In Rats Four Hours After Lmentioning
confidence: 99%
“…Fucoidan, a sulfated polyfucose polysaccharide found in the extracellular matrix of brown algae, exhibits biological properties, including antithrombotic, 1) antiinflammatory, [2][3][4] antiviral, 5,6) anti-adhesive, 7) and antitumor [8][9][10] activities, and it plays a role in modulating host immune systems, 11) arresting the cell cycle, and inducing apoptosis. 12) Recently, it was found that intraperitoneal injection and venous injection of fucoidan can rapidly mobilize hematopoietic stem/progenitor cells with long-term potential to repopulate the bone marrow in mice and monkeys.…”
mentioning
confidence: 99%
“…The vegetation-to-background uptake ratio was 5.2 (2.7-9.1). On autoradiography, the 99m Tc-fucoidan uptake ratio was 17 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Coregistration of autoradiography with histologic analysis performed after routine staining of tissue slices showed a clear delineation of the tracer uptake within the vegetations (Supplemental Fig.…”
Section: Endocarditic Vegetationsmentioning
confidence: 97%
“…Moreover, its pharmacologic effect as an in vivo selectin inhibitor has been assessed in various models of ischemia-reperfusion. After transient myocardial ischemia, fucoidan administration was associated with a decrease of neutrophil infiltration and pla-telet deposition in reperfused myocardium and finally reduced the extent of necrosis (16,17).…”
mentioning
confidence: 93%